STUDI TINGKAT PERKEMBANGAN TANAH PADA TOPOSEKUEN GUNUNG ANJASMORO, KABUPATEN MALANG, JAWA TIMUR - Singgih Waskita Putra; Abdul Mukri Prabowo; Mochtar Lutfi Rayes (Jurnal Tanah dan Sumberdaya Lahan, 2014)
In 1984, The Indonesian Government and The Netherlands established a project to characterized land and soil conditions of Kali Konto Watershed that highly human populated, due the planning procedure for forest land management model report. Few years after the project, several lands on the area were cultivated intensively due the commercial purposes. The research objectives were: 1) to observe and identify the physical land conditions on Mount Anjasmoro toposequence; 2) to study the soil morphological changes, especially during the land use changes, and 3) define the soils development within the last 20 years. A field research was established in September 2005, in the same location of 1984 research, which depended on landform variations, 5 pedons were taken, known as: KK 28 (Volcanic hill, upper slope), KK 27 (Volcanic colluvial valley, middle slope), KK 39 (Inter volcanic plain, lower slope), KK 40 (Intervolcanic plain, lower slope) and KK 41 (Inter volcanic plain), have been analyzed accurately included soil description and soil sampling. Soil profile descriptions and laboratory analysis showed that every pedons on the Anjasmoro toposequence were changed. Soil morphology changed during the land uses conversion and intensive land cultivations. Land use on KK 28 has changed from natural forest to agricultural dry lands for about 15 years, and the soil classification changed from Typic Hapludands to Andic Dystrudepts. KK 27 has the unchanged land use, which is as an agroforestry land, but has the soil classification changing, Andic Hapludolls to Typic Hapludolls. KK 39 has the land use changing, which only in addition of grass under growth of the main vegetations. Land use changing in KK 39 has the unchanged soil classification, which is Fluventic Hapludolls. KK 40 not only has the unchanged land use, but also soil classification, which is mix garden land for the land use, and the soil classification is Typic Argiudolls. KK 41 has the unchanged land use, which as rice fields, but has the soil classification changing, which is Typic Hapludalfs to Fragic Oxyaquic Hapludalfs